The hexed [compact disc, unabridged] - Graham, Heather (Graham, Heather. Krewe of hunters, 2014)
Craig Rockwell, known as Rocky, is a new member of the Krewe of Hunters, the FBI's team of paranormal investigators. He never got over finding a friend dead in the woods. Now another body's been found in those same woods, not far from the home of a woman named Devin Lyle. And Devin's been led to a third body, by; a ghost? Even as the danger mounts, Devin and Rocky begin to fall for each other, something the ghosts of Mina and past witches seem to approve of.